Alternative Policies in Managing the Karawang Healthy Service Program - Pirtha Agus Isnanti; Achmad Lukman Hakim (Sean Institute, 2025)
The management of the Karawang Healthy Service Program is still needed in Karawang Regency in order to guarantee health services for poor people who are not yet JKN participants and whose benefits are not guaranteed by JKN due to the possibility of changing the status of UHC Non Cut Off to UHC Cut Off in 2025, so it is necessarystrategy to prepare policies to control the utilization of Karawang Sehat services which has an impact on high service claims.The general objective of this research is to determine alternative policies for the Management of the Healthy Karawang Program by identifying and evaluating policies. through qualitative research design through case study methods and in-depth interviews and secondary document reviews. Sources of information were obtained from key informants and supporters. Data analysis using SWOT, Decision Tree Analysis and recommendation criteria according to William N Dunn (2020).